PENGARUH INVESTMENT OPPORTUNITY SET TERHADAP STRUKTUR MODAL DAN DAMPAKNYA TERHADAP RETURN SAHAM (Studi Pada perusahaan food and Beverages yang terdaftar di Bursa Efek Indonesia) - Kartika Aji; Nur Khusniyah I (Jurnal Ilmiah Mahasiswa FEB, 2014)
Investment is the number of funds or other resources  were done at this time, with the goal of obtaining a number of advantages  in the future. Basically the purpose of investors to invest is to get a return.  One alternative  investments can be made in the stock market. Stock returns  are  influenced by the rate  of growth and the company's  capital  structure policy. This study aims to determine the effect of investment opportunity set and capital structure to stock return, and the effect of investment opportunity set to capital structure. The population  used in this study are all food and beverages  company listed on the Indonesia   Stock  Exchange   during   the  period   2009-2014.   Sampling  with  purposive sampling method of determining  the sample with the criteria  that have been established and obtained a sample of 8 companies. The data analysis technique used is using partial least square method. The results  showed that the investment opportunity  set does not have a significant effect on stock returns,  while the capital  structure  does not have a significant  effect on stock returns  and  investment opportunity  set does not have a  significant  effect on the capital structure.   Keywords : stock return, investment opportunity set, capital structure